Role of inflammation in alcoholic liver diseases and its management - Sanglodkar, Uday (International Journal of Research in Medical Sciences, 2025)
Alcoholic liver disease (ALD) weighs a heavy health burden in India with 76% increase in disability-adjusted life years (DALYs) through 1990 to 2016. This review examines the role of inflammation in its pathogenesis and management approaches for the same. The pathophysiology of ALD involves various mechanisms such as increased gut permeability, oxidative stress and activation of inflammatory cascade, where tumor necrosis factor-alpha (TNF-α) plays a central role. Due to these varied mechanisms, the clinical presentation also varies, ranging from asymptomatic fatty liver to severe cirrhosis. As such, the management strategies range from alcohol abstinence and nutritional support to pharmacological interventions. For inflammation-predominant ALD phenotypes such as alcoholic hepatitis, corticosteroids are often used as the primary therapy. Other agents, including S-adenosylmethionine (SAMe), pentoxifylline and N-acetylcysteine, show promise in targeting the inflammatory pathogenesis of ALD. SAMe is a more specific option for targeting inflammation, while N-acetylcysteine is best used where its potent anti-oxidant activity is desired. Ultimately, liver transplantation offers the terminal option for end-stage disease, with considerations for inflammation to subside before it can be done. This review highlights the complex inflammatory mechanisms underlying the ALD spectrum and discusses various multimodal approaches for incorporating various treatment strategies.